Low-energy elastic electron interactions with pyrimidine - Palihawadana, P. (American Physical Society, 2011)
We present results of measurements and calculations of elastic electron scattering from pyrimidine in the energy range 3-50 eV. Absolute differential and integral elastic cross sections have been measured using a crossed electron-molecule beam spectrometer and the relative flow technique. The measured cross sections are compared with results of calculations using the well-known Schwinger variational technique and an independent-atom model. Agreement between the measured differential cross sections and the results of the Schwinger calculations is good at lower energies but less satisfactory at higher energies where inelastic channels that should be open are kept closed in the calculations.